Relationship of the Posterior Condylar Line and the Transepicondylar Axis: A CT-Based Evaluation - Fitz, David W.; Johnson, Daniel J.; Hartwell, Matthew J.; Sullivan, Ryan; Keller, Tyler J.; Manning, David W. (The Journal of Knee Surgery, 2020)
Posterior condylar referencing, a common method for determining femoral axial orientation during total knee arthroplasty (TKA), relies upon an assumed consistent relationship between the posterior condylar line (PCL) and the transepicondylar axis (TEA) of 3 degrees rotation. A total of 3,010 computed tomography (CT) scans and three-dimension (3D)-reconstructions for presurgical creation of patient-matched TKA instrumentation were analyzed. Demographic data and five anthropometric measurements (hip–knee angle [HKA], distal femoral angle [DFA], proximal tibial angle [PTA], tibial slope [TS], and PCL–TEA relationship) were recorded for each scan. A logistic regression model was fit to assess interaction between the PCL–TEA relationship and demographic and radiological variables. The mean (standard deviation [SD]) PCL–TEA was +2.9 degrees (0.8 degree). The range varied between +0.5 and +16.5 degrees. In 2,758 knees (91.6%), the PCL–TEA was within 3 ± 1 degrees, whereas 252 knees (8.4%) fell outside this range. There were no significant demographic or anthropometric differences between those knees with PCL–TEA relationship between 3 ± 1 degrees and those falling outside that range. The posterior condyles of diseased knees undergoing TKA can be reliably used to indirectly reference the TEA of the distal femur with an error of only 1 degree in 92% of patients.
Keywords: total knee arthroplasty; rotation; femoral component; referencing; computed tomography